Perbedaan Pendidikan Kesehatan Melalui Media Video Dan Booklet Terhadap Kemampuan Keluarga Dalam Melakukan Mobilisasi Dan Rom Pada Pasien Stroke - Nadila, Nadila; Amir, Yufitriana; Putri, Syeptri Agiani (Universitas Pahlawan Tuanku Tambusai, 2024)
Stroke patients need family help in mobilizing and ROM to prevent complications. Video media and booklets are media in providing health education that can increase the ability of families to mobilize and ROM in stroke patients. This study used an experimental quasy design with the Two group pre test-post test method. The research sample was 30 respondents with a purposive sampling technique. The bivariate analysis used was by the mc. nemar and ficsher's exact tests. The results of the fischer's exact test with a p value of 0.009 showed that there was a difference between health education, video media and booklets. As a medium in health education, video media and booklets both have an influence in improving the ability of families to mobilize and ROM in stroke patients. However, after being given the intervention video media is more effective compared to booklet media.